A Case of Fetal Tachycardia after Electroconvulsive Therapy: A Possible Effect of Maternal Hypoxia and Uterine Contractions. (4th July 2019) - Watanabe, Anri; Ayani, Nobutaka; Waratani, Miyoko; Hasegawa, Tatsuji; Ishii, Maki; Matsuoka, Teruyuki; Narumoto, Jin
Abstract : Electroconvulsive therapy (ECT) is considered to be an effective and safe treatment for depression in pregnant women in that it avoids the risk of psychotropic pharmacotherapy. However, clinicians should be cautious about the adverse effects in the fetus, such as fetal cardiac arrhythmia. Most of the previous studies have demonstrated a reduction in fetal heart rate associated with ECT. However, we encountered a case of fetal tachycardia after maternal ECT-induced convulsions. The patient was a woman who was 30 weeks' pregnant and had severe depression; fetal tachycardia (180–200 bpm) occurred immediately after the electrical stimulation and lasted for more than 30 minutes. The fetal tachycardia might have been caused by maternal hypoxia and uterine contractions. To our knowledge, this is the first report of fetal tachycardia as an adverse effect of ECT. Prolonged fetal tachycardia may cause fetal heart failure. Therefore, oxygenation during convulsions and careful fetal cardiac monitoring are essential when administering ECT in pregnancy.